Psikoedukasi Kesiapsiagaan Psikologis (Psychological Preparedness) Masyarakat Di Daerah Rawan Bencana Banjir Kampung Tegal Kota Parepare - Nurul Zakiah Almutmainna; Sitti Raodatuljannah; A. St. Latifah Humairah. A; Nur Zuhriya Djuhaepa; Asniar Khumas (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
This psychoeducation aims to educate the residents in disaster-prone areas about psychological preparedness. Psychological preparedness is the ability to manage and cope with emotional responses during disasters. What is meant is preparedness in behavior, feelings, and thoughts. Participants in this activity are survivors of flood disasters in Kampung Tegal. It is hoped that this psychoeducation can provide information and increase residents' understanding of the importance of psychological preparedness. This psychoeducation was attended by 30 residents or survivors in Tegal Village. The methods used include the stages of problem identification, providing education and evaluating activities through pre-post tests. The results of the analysis of Pre-test and Post-test data showed that after the implementation of the psychoeducation program, there was an increase in knowledge from residents related to psychological preparedness.